(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
A number of policies and standards regarding food safety issues and quality management have been established for the food industry. One of these requirements is related to the marking of food products describing the expiration date, content and quality. The report examines the possibility of using laser technology to mark chicken eggs. The contrast of the laser marking is the main criterion for determining its quality. The study examines the functional dependences of the contrast on the main technological parameters of the marking process: laser output power (7 – 20.3 W) and processing speed (50 - 300 mm/s). As a result of the research, optimal parameters for marking with a technological laser system CO2 have been determined.